Superficial preparation of biocompatible carbon quantum dots for antimicrobial applications. (2021) - Lakshmanan, A.; Surendran, P.; Manivannan, N.; Sathish, M.; Balalakshmi, C.; Suganthy, N.; Rameshkumar, P.; Kaviyarasu, K.; Ramalingam, G.
Abstract: Orange waste peel CQDs has been synthesized via simple hydrothermal method. The UV–visible spectrum shows near band edge absorbance and optical energy bandgap has been calculated as 3.44 eV and 5.60 eV. In addition, the antibacterial assay of CQDs was carried out against two kind of bacteria such as gram positive and gram-negative bacteria. It has been noted that the CQDs show good antibacterial activity towards the gram-negative bacterium Pseudomonas aeruginosa (ZOI: 30 mm). Antibacterial activity of natural waste CQDs was compared with chemically synthesized NPs and QDs.